Bathtub Dynamics Revisited: An Examination of Déformation Professionelle in Higher Education. (7th July 2016) - Kapmeier, Florian; Happach, Roland Maximilian; Tilebein, Meike
Abstract : It is assumed that more education leads to better understanding of complex systems. Some researchers, however, find indications that simple mechanisms like stocks and flows are not well understood even by people who have passed higher education. In this paper, we test people's understanding of complex systems with the widely studied stock‐and‐flow (SF) tasks. SF tasks assess people's understanding of the interplay between stocks and flows. We investigate SF failure of domain experts and novices in different knowledge domains. In particular, we compare performance on the original study's Bathtub task with the square wave pattern with two alternative cover stories from the engineering and business domains on different groups of business and engineering students from different semesters. Further, we show that, while engineering students perform better than business students, with progressing in higher education, students may lose the capability of dealing with simple SF tasks. We thus find hints on déformation professionelle in higher education. Copyright © 2016 John Wiley & Sons, Ltd.